2016
DOI: 10.1016/j.bjan.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Ocitocina em cesarianas. O que há de novo?

Abstract: Oxytocin is the uterotonic agent of choice in the prevention and treatment of postpartum uterine atony. Nevertheless, there is no consensus on the optimal dose and rate for use in cesarean sections. The use of high bolus doses (e.g., 10 IU of oxytocin) can determine deleterious cardiovascular changes for the patient, especially in situations of hypovolemia or low cardiac reserve. Furthermore, high doses of oxytocin for prolonged periods may lead to desensitization of oxytocin receptors in myometrium, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Yamaguchi et al . [5] observed that higher doses of oxytocin can cause receptor desensitization resulting ineffective action on uterine myometrium. In this study, the duration of the administration of oxytocin drip in the high-dose group was 8–12 h. Receptors became insensitive resulting the higher incidence of uterine atony in the high dose group with the longer duration of infusion the receptors became insensitive that will cause the uterine to be atony.…”
mentioning
confidence: 99%
“…Yamaguchi et al . [5] observed that higher doses of oxytocin can cause receptor desensitization resulting ineffective action on uterine myometrium. In this study, the duration of the administration of oxytocin drip in the high-dose group was 8–12 h. Receptors became insensitive resulting the higher incidence of uterine atony in the high dose group with the longer duration of infusion the receptors became insensitive that will cause the uterine to be atony.…”
mentioning
confidence: 99%